2006
DOI: 10.1245/s10434-006-9177-7
|View full text |Cite|
|
Sign up to set email alerts
|

Outcome of Metastatic GIST in the Era before Tyrosine Kinase Inhibitors

Abstract: Treatment with imatinib appears to improve 2-year survival of metastatic GIST by approximately 20% when compared to surgery alone. The combination of imatinib and surgery for the treatment of metastatic GIST therefore warrants investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(47 citation statements)
references
References 29 publications
4
43
0
Order By: Relevance
“…Although we found no statistically significant difference between the different organs involved (p=0.08), some studies 11,19,20 have shown that the GIST location directly influences the prognosis and those located in the stomach had more favorable course than those found in other topographies. Statistically, we found that the colonic topography directly influenced prognosis, since five out ofthe six tumors had unfavorable follow-up (metastasis/death), which was also found in another study 3 . The importance of tumor size in GIST prognosis has undergone major changes since the publication of Miettinen et al…”
Section: Discussion Discussion Discussion Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Although we found no statistically significant difference between the different organs involved (p=0.08), some studies 11,19,20 have shown that the GIST location directly influences the prognosis and those located in the stomach had more favorable course than those found in other topographies. Statistically, we found that the colonic topography directly influenced prognosis, since five out ofthe six tumors had unfavorable follow-up (metastasis/death), which was also found in another study 3 . The importance of tumor size in GIST prognosis has undergone major changes since the publication of Miettinen et al…”
Section: Discussion Discussion Discussion Discussionsupporting
confidence: 82%
“…G astrointestinal stromal tumors (GIST) are the most common mesenchymal neoplasms of the gastrointestinal tract 1 , their incidence being estimated at 14 to 20 cases per million population 2 ; they are more frequent in male patients older than 50 years old 3 . The pathogenesis is related to mutational changes in two tyrosine kinase receptors: KIT and PDGFR-alpha (plateletderived growth factor receptor alpha) on the surface of the interstitial cells of Cajal, the former being the most common (85% of cases) 4,5 .…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…genetic predisposition | sarcoma | pediatric G astrointestinal stromal tumor (GIST), the most common mesenchymal neoplasm of the gastrointestinal tract, is resistant to conventional cytotoxic chemotherapy (1). Oncogenic mutations in KIT or PDGFRA have been identified as central tumor-initiating events in many GISTs (2,3).…”
mentioning
confidence: 99%
“…Its exact incidence remains unknown, but is estimated at 14.5 cases per million in Sweden [3]. They commonly occur in people above the age of 50, with almost a similar distribution across the male and female gender [3,4]. GISTs are most commonly found in the stomach and small bowel, but they can occur in all other parts of the gastrointestinal tract as well as the abdominal and pelvic cavity.…”
Section: Introductionmentioning
confidence: 99%
“…It represents a revolution in the treatment of this notoriously chemotherapy-resistant tumour. Historically, the response rate to chemotherapy was very low, and the median survival for advanced disease was between 12 and 24 months [4,5,15]. Several phase 1 and 2 trials established the high efficacy and good tolerability of imatinib in treatment of GISTs [16][17][18].…”
Section: Introductionmentioning
confidence: 99%